2012
DOI: 10.1111/j.1744-6155.2012.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and barriers to dietary practices contributing to bone health among early adolescent Somali girls living in Minnesota

Abstract: Findings provide the foundation for the development of culturally relevant promotion of foods rich in calcium and vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Future interventions should create an environment where both children and adolescents receive education about calcium and its health-related outcomes. As suggested by previous studies, culture and traditions play an important role in shaping dietary practices, which cannot be overlooked (61) . The combination of positive parental influence and development of habits from early childhood are likely to result in a positive impact and a continuation of dietary habits in young adulthood.…”
Section: Discussionmentioning
confidence: 89%
“…Future interventions should create an environment where both children and adolescents receive education about calcium and its health-related outcomes. As suggested by previous studies, culture and traditions play an important role in shaping dietary practices, which cannot be overlooked (61) . The combination of positive parental influence and development of habits from early childhood are likely to result in a positive impact and a continuation of dietary habits in young adulthood.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, some immigrants to Italy are less likely to have breakfast compared to Italians [75]. Conversely, AMC in Norway appear to align with Norwegian dietary recommendations [76], and AMC in the United States make dietary choices that are highly influenced by their culture [77]. Factors associated with child hunger and food insecurity include poor English proficiency and shorter length of stay in the host country [78,79].…”
Section: Nutritionmentioning
confidence: 99%
“…Of those, almost 38% found that higher acculturation was related to beneficial health impacts [14,23,24,25,26,27,28,29,30,31,32], whereas 48% found that higher acculturation was linked to adverse health impacts [17,33,34,35,36,37,38,39,40,41,42,43,44,45]. Results also indicated that 14% of the studies had mixed results [46,47,48,49] and 6% had either non-significant results [50] or suggestive results from qualitative analyses of focus groups [51]. Interestingly, culture of origin did not offer an explanation for the variation on whether the statistical relationship was positive or negative.…”
Section: Resultsmentioning
confidence: 99%